2020
DOI: 10.3389/fnins.2020.586424
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Modulation With Low-Intensity Focused Ultrasound Stimulation to the Vagus Nerve: A Pilot Animal Study

Abstract: Objective For hypertensive individuals, their blood pressure (BP) is often managed by taking medications. However, antihypertensive drugs might cause adverse effects such as congestive heart failure and are ineffective in significant numbers of the hypertensive population. As an alternative method for hypertension management, non-drug devices-based neuromodulation approaches such as functional electrical stimulation (FES) have been proposed. The FES approach requires the implantation of a stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This acute reduction in BP was previously demonstrated when selective and non-selective VNS therapy was performed to anesthetized rats ( Plachta et al, 2014 , 2016 ). Low-intensity focused ultrasound VNS technique also reduced BP and HR in rabbits ( Ji et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This acute reduction in BP was previously demonstrated when selective and non-selective VNS therapy was performed to anesthetized rats ( Plachta et al, 2014 , 2016 ). Low-intensity focused ultrasound VNS technique also reduced BP and HR in rabbits ( Ji et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, targeting the core nucleus of the autonomic neural network and inhibiting SNS activity may have beneficial effects on hypertension. For example, baroreceptor stimulation by baroreflex activation therapy [44], rostral subcallosal neocortex stimulation by DBS [45], vagus nerve stimulation by LIFU [46], and kidney stimulation by LIFU [47] all reported antihypertensive effects. This VLPAG is involved in the integration of autonomic nerve function, with strong functional brain connections to the solitary tract nucleus and medulla oblongata regions [48].…”
Section: Discussionmentioning
confidence: 99%
“…Ji and colleagues demonstrated that low-intensity FUS of the vagus nerve was capable of lowering blood pressure in normotensive animals [11]. In a study published in the Journal of Neural Engineering [12], the same group investigated the effect of FUS of the left vagus nerve on blood pressure, heart rate, respiratory rate, heart rate variability (HRV), systolic blood pressure variability, and baroreflex sensitivity (BRS) in fifty 12-week-old spontaneously hypertensive rats.…”
Section: Focused Ultrasound To Modulate the Activity Of The Autonomic...mentioning
confidence: 99%